Rahsia kejayaan menulis jurnal berimpak tinggi, buku dan tesis - Roslan Abd. Shukor 1961- (Penerbit Universiti Kebangsaan Malaysia, 2015)
This book is written for researcher and student on how to write a manuscript for a refereed journal, book and thesis.